2014
DOI: 10.1182/blood-2013-05-500496
|View full text |Cite
|
Sign up to set email alerts
|

CXCR7 participates in CXCL12-induced CD34+ cell cycling through β-arrestin–dependent Akt activation

Abstract: Key Points• CXCR7 is a key actor of the cell cycling and survival promoting effect of CXCL12 on primary human CD34 In addition to its well-known effect on migration and homing of hematopoietic stem/ progenitor cells (HSPCs), CXCL12 chemokine also exhibits a cell cycle and survivalpromoting factor for human CD34 1 HSPCs. CXCR4 was suggested to be responsible for CXCL12-induced biological effects until the recent discovery of its second receptor, CXCR7. Until now, the participation of CXCR7 in CXCL12-induced HSP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 43 publications
(75 reference statements)
2
38
0
Order By: Relevance
“…The arrestin scaffolds may serve as adapter molecules to assemble multi-protein complexes ultimately leading to receptor internalization, recycling back to the plasma membrane, and downstream signaling events, including ERK1/2 (extracellular signal-regulated kinases) activation [911]. Arrestins may also shuttle between the cell nucleus and cytoplasm [12]. This process is not fully elucidated for CXCR7.…”
Section: Introductionmentioning
confidence: 99%
“…The arrestin scaffolds may serve as adapter molecules to assemble multi-protein complexes ultimately leading to receptor internalization, recycling back to the plasma membrane, and downstream signaling events, including ERK1/2 (extracellular signal-regulated kinases) activation [911]. Arrestins may also shuttle between the cell nucleus and cytoplasm [12]. This process is not fully elucidated for CXCR7.…”
Section: Introductionmentioning
confidence: 99%
“…8 The activity of CXCL12 is mediated by binding of the chemokine to its receptors (CXCR4 and CXCR7) on circulating hematopoietic cells. 9,10 Experimental evidence has accumulated on the crucial role of the CXCL12/CXCR4 axis in the bone marrow niche. Sugijama et al demonstrated that abrogation of CXCL12/CXCR4 signaling is associated with a reduction in HSPC numbers.…”
Section: Introductionmentioning
confidence: 99%
“…From these results we concluded that the HSC potential of the Tarnowski et al, 2010;Torossian et al, 2014). First trimester CD34 ++ CD45 low chorion cells expressed low levels of CXCR7 (ACKR3) and no detectable CD193 (CCR3) and CD195 (CCR5), but expression of the receptors increased in second trimester samples (Fig.…”
Section: Sorted Cd34mentioning
confidence: 80%
“…CD195 is expressed at higher levels on cord blood HSCs than on those obtained from BM or mobilized to peripheral blood (Rosu-Myles et al, 2000). CXCR7, another CXCL12 receptor (Tarnowski et al, 2010), cooperates with CD184 in enhancing the effects of CXCL12 on cell cycling, survival and proliferation of CD34 + cells from peripheral blood (Torossian et al, 2014). In addition, CD34 + cells from umbilical cord blood express CD193 (Lamkhioued et al, 2003), and CD191 expression by CD34 + cells in cord blood confers superior engraftment of immunodeficient mice (de Wynter et al, 2001 .…”
Section: Discussionmentioning
confidence: 99%